IMPLEMENTASI MODEL PEMBELAJARAN PROJECT BASED LEARNING BERBANTUAN MEDIA YOUTUBE PADA MATERI TEKS BERITA SISWA KELAS VII SMP NEGERI 7 MEDAN - Richo Adjie Santana; M. Oky Fardian Gafari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This descriptive qualitative research with a case study method aims to describe the implementation of the Project Based Learning (PjBL) model assisted by YouTube media on news text material for grade VII students of SMP Negeri 7 Medan. This research is motivated by low writing skills, student learning motivation, and monotonous teacher approach. Data were collected through observations, interviews, ARCS motivational questionnaires, and documentation. The results of the study showed that learning activities were interactive and conducive according to the entire PjBL syntax. The implementation of this model has been proven to increase students' learning motivation (especially the aspects of relevance and satisfaction) and significantly boost the learning outcomes of writing news texts. This can be seen from the drastic decrease in the number of students under the KKM (from 16 to 7 students), the lowest increase in scores (58 to 72), and the highest scores (90 to 95). The YouTube assisted PjBL model is effective in improving students' motivation and writing skills.